A RARE CASE OF COLORECTAL CARCINOMA WITH BONY METASTASES - Muhammad Inuwa Mustapha; Mustapha Ibrahim Usman (Ntec Specialist, 2021)
Colorectal cancer is one of the most common malignancies in the world. Bone metastasis is rare, and data are lacking. Here we report a case of colorectal carcinoma with bony metastasis.